AUDIT COMMITTEE, COMPANY SIZE AND IMPLEMENTING OF INTERNAL AUDIT - Icih Icih; Norhanizah Johari; Ajeng Rindi Antika; Bambang Sugiharto (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2024)
Audit Committee Chair Internal Overlap is the dual position of the Audit Committee which is more than one board committee in one company, Audit Committee Chair External Overlap is the dual position of the Audit Committee who holds the position of director in another public company or serves as a leader in another company. Chair expertise is an individual who has education and experience in accounting or auditing. And Committee Meetings are the number of meetings held by the audit committee during the financial year. Then firm size plays an important role in applied microeconomics and industrial organization. Implementation of Internal Audit is an activity of providing assurance and consulting that is independent and objective, with the aim of increasing value and improving company operations. This study uses secondary data sources. This study carried out a sampling technique using purposive sampling as the sample. The data analysis method used is logistic regression analysis with the help of SPSS software data processing. Based on the results of the Audit Committee Chair Internal Overlap research has a negative effect on the Implementation of Internal Audit, this concurrent position causes a decrease or weakening of the quality of internal audit within a company. Audit Committee Chair External Overlap has no effect on Internal Audit Implementation, Chair Expertise has a positive effect on Internal Audit Implementation, Committee Meetings (X4) have no effect on Internal Audit Implementation, Company Size (X5) has no effect on Internal Audit Implementation, independent variable has significant effect simultaneously on the dependent variable.